Effects of a food preparation program on dietary well-being for stroke patients with dysphagia: A pilot study - Lin, Shu-Chi (Medicine (Baltimore), 2021)
BACKGROUND: Dysphagia is one of the common issues observed in patients with stroke. Stroke patients with dysphagia have to eat blended food or similar types of food for each meal, resulting in dietary dissatisfaction. The purpose of this study was to investigate the effects of a food preparation program on dietary well-being for stroke patients with dysphagia. METHODS: This study was a pilot randomized clinical trial. Twenty-two patients were assigned randomly into the food preparation group (n = 11) and control group (n = 11). The food preparation group received oral motor exercises, recognition of food texture and thickener, and hands-on food preparation for 6 weeks. Outcome measures included the Dietary Well-Being Scale, brief version of the World Health Organization Quality of life, Swallowing Quality of Life Questionnaire, and Mini Nutritional Assessment. RESULTS: Patients in the food preparation group showed significant improvements in the Dietary Well-Being Scale, psychological and environmental domains of the brief version of the World Health Organization Quality of life (P = .001–.024) with small to large effect sizes (success rate difference = 0.23–0.46). The Swallowing Quality of Life Questionnaire and Mini Nutritional Assessment displayed non-significant differences (P = .053–.092) and revealed small to moderate effect sizes (success rate difference = 0.23–0.32). CONCLUSIONS: The food preparation program showed a positive impact on dietary well-being and a potential improvement in the health-related quality of life, quality of life related to the process of swallowing, and nutritional status for stroke patients with dysphagia. We recommend that stroke patients with dysphagia receive adequate knowledge and hands-on food preparation training to increase their dietary intake and well-being.